Reconfiguring discourse to attend to interrelation: a rhetorical analysis of kelp agency in scientific texts - Anderson, Jennifer, author; Szymanski, Erika, advisor; Amidon, Timothy, committee member; Hall, Ed, committee member (Colorado State University. Libraries, 2020)
The purpose of this thesis is to consider how thinking-with kelp ecologies in knowledge-making practices opens opportunities for attending to the co-becoming of species through interrelations. In this thesis, I consider how scientific discourse practices constitute relations with kelp forests and how constitutions can change to think-with kelp forests as actors in knowledge-building. I argue this reconstitution is important for changing asymmetries in power over and cognitive distance from kelp ecosystems. Using critical discourse analysis, this thesis considers how scientific discourse practices constitute power hierarchies between kelp ecosystems and humans. Then, this thesis reads the power hierarchies through an ecological approach to rhetoric to trace how kelp forests produce relations through interactions with environmental processes and a diverse range of species actors. Through the rhetorical analysis, this thesis considers how thinking-with kelp forests can open opportunities for research and discourse practices to attend to co-constituting webs of interrelations. Finally, this thesis considers how embodied experiences with kelp forests open opportunities for researchers to notice and to respond to—to think-with—what matters for a kelp forest. This thesis responds to the modernist bifurcation of language and materiality, subject and object, mind and body. It considers how communication and knowledge-building can make-with the world today by attending to how all planetary actors are of the world through interrelationships with it.